The DOWN Questionnaire: A Novel Screening Tool for Cervical Spondylotic Myelopathy. Issue 6 (September 2019) - Barkoh, Kaku; Ohiorhenuan, Ifije E.; Lee, Larry; Lucas, Joshua; Arakelyan, Anush; Ornelas, Christopher; Buser, Zorica; Hsieh, Patrick; Acosta, Frank; Liu, John; Wang, Jeffrey C.; Hah, Raymond
Study Design: Case-control study. Objectives: Cervical spondylotic myelopathy (CSM) is the most common cause of spinal cord injury in adults aged over 55 years. However, since the onset is typically insidious, accurately diagnosing CSM can be challenging, often requiring referral to a subspecialist and advanced imaging. To help identify patients at risk for CSM, this case-control study compared responses to a series of 4 questions (DOWN questionnaire) in myelopathic and non-myelopathic patients. Methods: Ninety-two patients, 46 with and 46 without myelopathy, were recruited for the study. Each patient answered 4 questions encompassing common symptoms associated with CSM. Responses between patient groups were compared, and Cohen's κ was used to assess for agreement between responses and the diagnosis of myelopathy. Results: We found a sensitivity of 91% and a κ of 0.54 to 3 positive responses and a sensitivity of 72% and a κ of 0.61 to 4 positive responses. Conclusions: Positive responses to 3 or more DOWN questions has high sensitivity and moderate agreement with the diagnosis of myelopathy based on history, physical exam, and review of advanced imaging by an orthopedic or neurological surgeon. The DOWN questionnaire is a potentially useful screening tool to identify patients at risk for CSM.